Wnt signaling in bone formation and its therapeutic potential for bone diseases. (February 2013) - Kim, Jeong Hwan; Liu, Xing; Wang, Jinhua; Chen, Xiang; Zhang, Hongyu; Kim, Stephanie H.; Cui, Jing; Li, Ruidong; Zhang, Wenwen; Kong, Yuhan; Zhang, Jiye; Shui, Wei; et al.
The Wnt signaling pathway plays an important role not only in embryonic development but also in the maintenance and differentiation of the stem cells in adulthood. In particular, Wnt signaling has been shown as an important regulatory pathway in the osteogenic differentiation of mesenchymal stem cells. Induction of the Wnt signaling pathway promotes bone formation while inactivation of the pathway leads to osteopenic states. Our current understanding of Wnt signaling in osteogenesis elucidates the molecular mechanisms of classic osteogenic pathologies. Activating and inactivating aberrations of the canonical Wnt signaling pathway in osteogenesis results in sclerosteosis and osteoporosis respectively. Recent studies have sought to target the Wnt signaling pathway to treat osteogenic disorders. Potential therapeutic approaches attempt to stimulate the Wnt signaling pathway by upregulating the intracellular mediators of the Wnt signaling cascade and inhibiting the endogenous antagonists of the pathway. Antibodies against endogenous antagonists, such as sclerostin and dickkopf-1, have demonstrated promising results in promoting bone formation and fracture healing. Lithium, an inhibitor of glycogen synthase kinase 3β, has also been reported to stimulate osteogenesis by stabilizing β catenin. Although manipulating the Wnt signaling pathway has abundant therapeutic potential, it requires cautious approach due to risks of tumorigenesis. The present review discusses the role of the Wnt signaling pathway in osteogenesis and examines its targeted therapeutic potential.